Using the buck-interleaved buck–boost converter to implement a step-up/down inverter. Issue 2 (18th April 2017) - Chang, Chien-Hsuan; Cheng, Hung-Liang; Chang, En-Chih
Abstract : Purpose: A typical photovoltaic grid-connection power system usually consists of multi-stage converters to perform multiple functions simultaneously. To simplify system configuration, reduce cost and improve conversion efficiency, this paper aims to develop a buck–boost-type inverter. The proposed inverter has both step-up and step-down functions, so that it is suitable for applications with wide voltage variation. As only one power switch operates with high frequency at one time, switching losses can significantly be reduced. Design/methodology/approach: A step-up/down inverter is developed by adopting a buck-interleaved buck–boost (BuIBB) DC-DC converter and connecting with an H-bridge unfolding circuit with line-commutated operation. Finding: The proposed circuit can work functionally as either a buck-type or boost-type inverter, so that partial energy can be directly delivered to output to improve efficiency. The input current is shared by two inductors, leading to the reduction of current stresses. Research limitations/implications: To apply the proposed inverter to micro-inverter applications in the future, developing a step-up/down inverter with a higher conversion ratio will be considered. Practical implications: A laboratory prototype is built accordingly to verify the feasibility of the proposed inverter. The experimental results are presented to show the effectiveness. Originality/value: This paper proposes a step-up/down inverter by using the BuIBB converter, which is innovatively studied.